Consensus Statements on the Use of High-Sensitivity Troponin I as the Assessment of Cardiac Risk in Apparently Healthy Population in Indonesia - Ambari, Ade Meidian; Ng, Sunanto; Rejeki, Vidya Gilang; Rina Artha, I Made Junior; Raynaldo, Abdul Halim; Alsagaff, Mochamad Yusuf; Wicaksono, Sony Hilal; Dwiputra, Bambang; Desandri, Dwita Rian (The Indonesian Heart Association, 2023)
Cardiovascular disease (CVD) is a growing burden in Indonesia, making primary prevention of utmost importance. High sensitivity cardiac troponin I (hsTnI) has been known as one of the biomarkers of choice for diagnosing acute myocardial infarction. Nonetheless, recent studies indicate that hsTnI assay has potential as a predictor of cardiac risk in asymptomatic individuals. An advisory board consisting of renowned cardiologists from the Indonesian Heart Association was convened in Jakarta in March 2023. The meeting aimed to explore the appropriate use of hsTnI for cardiovascular (CV) risk stratification in apparently healthy adults in Indonesia. The board reviewed relevant literature and developed key consensus statements, including hsTnI cut-off for identifying high-risk asymptomatic patients, the proposed algorithm, and monitoring after aggressive risk factor control. This article presents the resulting consensus statements to provide clinicians with a practical tool for planning primary prevention strategies. Furthermore, it is expected to raise awareness and advocacy among stakeholders in the healthcare infrastructure regarding the use of hsTnI as a guide for assessing CV risk in Indonesia.